2017
DOI: 10.1016/j.jjcc.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Embolic Risk French Calculator for symptomatic embolism with infective endocarditis among Japanese population

Abstract: The ER-Calculator is a useful predictor of new SE. Predictive ability is more remarkable for critical embolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…All studies (except for one) counted systemic emboli as EEs; twelve studies also included pulmonary emboli [3,5,6,21,30,32,36,44,46,48,53,57], two studies included cutaneous emboli [6,29] and four studies included silent emboli [31,43,49,60]. Twelve studies included only new EEs occurring after admission or antibiotic therapy initiation [3,11,12,21,24,32,37,39,41,42,44,56], and two studies excluded EEs occurring after cardiac surgery [3,26]. One study did not define EEs [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies (except for one) counted systemic emboli as EEs; twelve studies also included pulmonary emboli [3,5,6,21,30,32,36,44,46,48,53,57], two studies included cutaneous emboli [6,29] and four studies included silent emboli [31,43,49,60]. Twelve studies included only new EEs occurring after admission or antibiotic therapy initiation [3,11,12,21,24,32,37,39,41,42,44,56], and two studies excluded EEs occurring after cardiac surgery [3,26]. One study did not define EEs [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among 11 studies including patients with EEs occurring at various times and reporting data, the overall proportion of patients with EEs whose embolism occurred before initiation of antibiotics was 53.3% (95% CI 38.0%e68.1%; see Supplementary material, Fig. S2) [3,6,8,11,13,26,28,30,43,44,56]. Of 34 studies pooled in meta-analyses of echocardiographic characteristics, six used transthoracic echocardiography [24,27,30,36,58,59], six used trans-oesophageal echocardiography [6,8,21,26,34,52], 16 used both [3,5,11,22,23,31e33, 37,44,46,48,49,53,56,57], and six did not specify the modality [13,28,45,47,51,55].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…They found that a probability on the 28th hospital day >7% was closely associated with the in-hospital embolic risk. In contrast, Takahashi et al (12) defined a probability on the 14th hospital day >8% as indicative of a high risk and demonstrated that the incidence of new embolic events during a 12-week observation period was significantly higher in the high-risk group than in the low-risk group. Thus, the probability on the 14th hospital day may predict longer-term outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, we did not assess the prothrombic activity in the present study. Fourth, we used a probability >8% as the cut-off value for the high-risk group, according to a previous report (12). Alternatively, we could have independently determined the optimal cut-off value using a receiver operating characteristic curve analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation